2009
DOI: 10.1111/j.1365-2982.2009.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell death results in hyperganglionosis: implications for enteric nervous system development

Abstract: The enteric nervous system (ENS) is derived from vagal and sacral neural crest cells (NCC) that delaminate from the neural tube and undergo extensive migration and proliferation in order to colonize the entire length of the gut and differentiate into many millions of neurons and glial cells. Although apoptotic programmed cell death is an essential physiological process during development of the majority of the vertebrate nervous system, apoptosis within early ENS development has not been comprehensively invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 52 publications
(67 reference statements)
1
26
1
Order By: Relevance
“…This behavior strongly suggests that cell elimination does occur among migrating ENPs populating the intestine. Given the role of programmed cell death in neurons and proliferating neural precursors (Enomoto, 2009) and a recent report that that inhibition of cell death leads to hyperganglionosis of the foregut (Wallace et al ., 2009), this elimination process likely plays a critical role in normal development of the ENS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior strongly suggests that cell elimination does occur among migrating ENPs populating the intestine. Given the role of programmed cell death in neurons and proliferating neural precursors (Enomoto, 2009) and a recent report that that inhibition of cell death leads to hyperganglionosis of the foregut (Wallace et al ., 2009), this elimination process likely plays a critical role in normal development of the ENS.…”
Section: Resultsmentioning
confidence: 99%
“…Cells exhibiting nuclear fragmentation were observed at a relatively low frequency, 0.7-3% of total Sox10 -H2BVenus+ cells in each viewing field exhibited fragmenting nuclei in images taken every 15-20 minutes. Multiple efforts have been made previously to identify apoptosis of ENPs in the developing intestine using static methods (Gianino et al ., 2003; Kruger et al ., 2003; Maka et al ., 2005; Wallace et al ., 2009; Wallace et al ., 2010). Only a single study has previously identified apoptotic cells within the walls of the fetal gut using static methods and established that approximately 0.2% of all Sox10+ cells were caspase3+ throughout the length of the fetal gut at 11.5dpc (Wallace et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that both cell death and proliferation play important roles in the normal development of the ENS (20,56,68,69). Proliferation is essential for the migration of ENS progenitors (63), and some of the genes associated with Hirschsprung disease play a role in proliferation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Sacral NCCs make a small contribution of neurons and glial cells by colonizing the hindgut at E15.5 (Druckenbrod and Epstein 2005). Different cellular processes such as neural crest specification, proliferation, differentiation, and migration are important for complete innervation of the gut (Asai et al 2006;Simpson et al 2007;Okamura and Saga 2008;Wallace et al 2009). The study of enteric NCC (ENCC) migration has revealed complex cellular behaviors at the migratory wave front.…”
mentioning
confidence: 99%